SATB2 gene variants in non-syndromic cleft lip with or without cleft palate in Indian population - Venkatesh Babu Gurramkonda; Altaf Hussain Syed; Jyotsna Murthy; Bhaskar V.K.S. Lakkakula (Elsevier, 2015)
Objectives: Non-syndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common craniofacial birth defects and little is known about its aetiology. Initial studies of cytogenetic analysis provided the clues for possible genes involved in the pathogenesis of NSCL/P. This approach led to the identification of SATB2 gene on 2q32-q33. The aim of this study was to determine the association between SATB2 mutations and NSCL/P. Materials and methods: The rs137853127, rs200074373 and rs1992950 mutations of the SATB2 gene were investigated in 173 patients with NSCL/P and 176 normal controls using Kbioscience KASPar chemistry, which is a competitive allele-specific PCR SNP genotyping system. Results: The mutations in exon 6 (rs137853127 and rs200074373) were monomorphic, the intronic variant (rs1992950) was polymorphic and genotype distribution was in agreement with Hardy-Weinberg equilibrium. The rs1992950 genotype distribution is not statistically significant between NSCL/P and controls. Conclusion: Our findings suggest that the SATB2 gene variations do not contribute to the development of NSCL/P in the south Indian population.